Математическая модель гидравлического сопротивления и теплопроводности каталитических сред - Любчик, Леонид Михайлович; Ведь, Елена Валерьевна (НТУ "ХПИ", 2013)
The models of hydraulic resistance and thermal conductivity for the interior spaces of various catalytic media were given in this article. The resulting model describes the hydrodynamic and heat and mass transfer behavior of the gas mixture in the reaction of carbon monoxide oxidation in the boundary layers has been developed.
Keywords: смесь газовая; модель гидродинамическая; доокисление; катализ; тепломассообмен